أثر استراتيجية كيلر في الفهم القرائي لمادة الأدب والنصوص عند طلاب الصف الخامس الإعدادي (Journal of the College of Basic Education, 2024)
The aim of the research is to identify the effect of Keller's strategy in developing reading comprehension of literature and texts for fifth-grade middle school students. To achieve this goal, the experimental approach was adopted and the sample consisted of 60 students who were distributed into two groups, a control and an experimental group (30 in each group). A reading comprehension test for the literature and texts subject was prepared from 20 multiple-choice paragraphs. The research results showed that the experimental group that was taught using Keller's strategy outperformed the control group that was taught using the traditional methods in the reading comprehension test for the literature and texts subject. The researcher recommended using Keller's strategy to master reading comprehension skills and all skills of the branches of the Arabic language.